Thyrotoxicosis: A paradox - Himmatrao S. Bawaskar; Pramodini H. Bawaskar (Journal of Family Medicine and Primary Care, 2023)
Incidence of thyroid dysfunctions including hypo- or hyperthyroidism is significantly increased. Hyperthyroidism is common in males, and hypothyroidism is often seen in females. Here, we report two female patients suffering from hyperthyroidism, but their signs and symptoms are totally opposite to each other.